ANALISIS KOMPARASI USAHATANI PADI SAWAH SISTEM TANAM SRI DAN KONVENSIONAL DI DESA BUKIT PENINJAUAN I KECAMATAN SUKARAJA KABUPATEN SELUMA - Tinurbaya L, Evi; Priyono, Basuki Sigit; Rasyid, Witman (Jurnal AGRISEP, 2011)
SRI is rice cultivation technique which able increase rice productivity by modify plant management, soil, water, and nutrients. The goal of this research are to determine and analyze the factors which influence the production, and to know the revenue between SRI method and Conventional system of rice farm. Rice farm revenueby SRI method is Rp 4.199.923,53 /Ut/Mt or Rp 6.287.124,48 /Ha/Mt while the farmers in convensional system is Rp 4.761.240,60/Ut/Mt or Rp 6.343.424,53/Ha/Mt. “Cobb-douglass” analysis used to determine someproduction factors which invluence the production.The study result explain that factorwhich influence to the production of SRI system is land area, while the amount of seeds, organic fertilizer, organic pesticides, and the labor had no effect in rice farm production. Where as the factorswhich significantly influence to the  productionof conventional system are land area and labor, while the amount of seeds, chemical fertilizer, and  chemical pesticides had no effect in rice farm production. Key words: SRI method, Production factors, Rice farm revenue